BBC Horizon - Inside Chernobyl's Sarcophagus - Briffa, Edward (United Kingdom : BBC, 1996)
Updating the original award winning programme, this HORIZON Special looks at what has changed at Chernobyl 10 years after the world's worst nuclear accident. With the concrete sarcophagus still crumbling the future of the power station remains uncertain. This video traces three of the original scientists from the investigation team who talk openly about their findings, what has since happened and what remains to be done. At the same time, the documentary deals with the consequences upon these people's life of their heroic activity and research in the immediate proximity of the sarcophagus.
Duration: 00:50:00